Prioritizing Waqf Core Principles (WCP) Criteria - Mujahidah, Anisa Syahidah (Islamic Social Finance, 2023)
A waqf institution is a social organization that acts as an intermediary between wakif and mauquf alaih or people who are entitled to receive waqf benefits. The waqf core principle (WCP) is a starting point as a framework and best practice standard for waqf-based governance. The waqf core principle is intended to improve the quality of waqf students by identifying these weaknesses in supervision and regulation. This study tries to prioritize the WCP principles and also the important criteria from each level using the Analytica Hierarchy Process (AHP). There are five core principles in this WCP, which consist of: the legal basis, waqf supervision, good, and correct Nazir governance, risk management, and the application of sharia principles in governance. Of these principles, the main priority is the application of sharia principles in waqf governance. The recommendation for waqf practitioners or managers is to apply this WCP optimally, according to the priority level according to the results of this study.